P526 Early sonographic response predicts long-term outcome in Crohn's disease: A prospective cohort study. (16th January 2018) - Novak, K; Halasz, J; Lu, C; Kaplan, G; Seow, C; Tanyingoh, D; Devlin, S; Panaccione, R; Wilson, S
Abstract: Background: Measures of early treatment response are shown to predict long-term outcomes in Crohn's disease (CD). Early optimisation of therapy in CD may lead to better outcomes both early and late in the disease. The aim of this study is to evaluate ultrasound (US) response to induction treatment with adalimumab (ADA), with long-term follow-up to determine sonographic predictors of outcome. Methods: Prospective, single-centre cohort study in patients with known CD recruited from January 1, 2011 to December 31, 2014, having active CD with induction and maintenance therapy with ADA. Patients had US pre-treatment, at 3 and 6 months. Patients underwent pre-treatment ileocolonoscopy (IC) within 14 days of US. A subset had repeat IC at 6 months. The simple ultrasound score (SUS–based on bowel wall thickness and hyperaemia) and the Simple Endoscopic Score (SES)/Rutgeert's score were recorded at each interval. Response at 6 months was characterised as complete, partial or non-response based on US parameters. Follow-up evaluated medical management, hospitalisation and surgery for 3 (maximum 6) years. Results: There were 42 patients included, 62% (26 of 42) female, 38% (16 of 42) male with a mean age of 42 years (Table 1). Disease distribution: ileal 38% (16 of 42), 55% (23 of 42) ileocolonic and 7% (3 of 42) with colonic disease. All patients exhibited activity on US at baseline, with a mean SUS 3.15 (out of 4.63). SES was completed for 21 of 42 patients, mean 6.57, and Rutgeert's score (10 of 42 patients) mean 3.20, while 19% were not amenable to endoscopic scoring (8 of 42) and 5% (2 of 42) had no baseline IC. At 6 months, 62% (26 of 42) were US responders, 10 of 26 with complete response (BWT ≤5mm). The remainder was not improved (38%). In the follow-up period, more complete responders than non-responders remained on ADA ( p = 0.04), but partial responders and non-responders were not significantly different ( p = 0.29). Surgery rate was 31% in non-responders, compared with 44% of partial responders ( p = 0.72) and 10% of complete responders ( p = 0.35). This patient however stopped medication before surgery with disease progression. Among all surgery patients, 85% (11 of 13) had severe disease on US with BWT ≥7mm and/or sonographic complications (strictures/penetrating complications). Conclusions: Early, robust sonographic response predicts long-term treatment success and surgical avoidance in patients with CD. The presence of complications on baseline US suggests a trend towards treatment failure and need for surgery. Future evaluation of inflammatory vs. stricturing/penetrating disease may be important.